2007
DOI: 10.1111/j.1365-2230.2007.02414.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of an educational programme to improve the skills of general practitioners in diagnosing melanocytic/pigmented lesions

Abstract: The education programme improved the malignant : benign ratio of melanocytic lesions, resulting in a doubling in the number of melanomas diagnosed. We found that GPs with less experience benefited most from the programme, indicating that tailoring of programmes to individual skills and years of practice might be beneficial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 15 publications
(28 reference statements)
2
40
1
Order By: Relevance
“…For example, instruction on management options ranged from triage and specialist referral to biopsies and definitive surgical management. The Basic Skin Cancer Triage course, Skin Watch program, and the Melanoma Education for Primary Care program were notable for including five of six curricular components, presenting very thorough descriptions of the educational components, and undergoing repeated evaluation [33][34][35][36][37][38][39] . The aforementioned interventions each received funding on a national level or from large independent funds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, instruction on management options ranged from triage and specialist referral to biopsies and definitive surgical management. The Basic Skin Cancer Triage course, Skin Watch program, and the Melanoma Education for Primary Care program were notable for including five of six curricular components, presenting very thorough descriptions of the educational components, and undergoing repeated evaluation [33][34][35][36][37][38][39] . The aforementioned interventions each received funding on a national level or from large independent funds.…”
Section: Discussionmentioning
confidence: 99%
“…The aforementioned interventions each received funding on a national level or from large independent funds. Dermoscopy is a recent and novel addition to a PCP skin cancer curriculum, being a component of the curriculum for only two interventions and first appearing as part of an intervention in 2006 34,40 . The decision to introduce dermoscopy to nondermatologists and the best method to teach it have been debated, given that it is difficult to learn without formal training 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies had a high risk of selection bias, [13][14][15][16][17]19,20,22,24,25,27,[29][30][31] with little information given (if any) about whether those who participated were different from those who chose not to take part. Almost all studies reported a follow-up period of less than 1 year; 11,14,[17][18][19]21,23,24,27,28,31,33 several tested participants straight after the intervention; 15,16,29,30 and some did not include or state any follow-up period. 20,22,25,32 Therefore, it cannot be determined whether any of the reported improvements persisted.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The low-quality before-and-after studies did show significant improvement in outcomes. 17,33 Decision-support software and guideline use Four studies, including three good-quality RCTs, tested computer-based interventions to change PHP behaviour. 20,23,26,32 These studies were designed to improve the quality of referrals to secondary care as a proxy to reducing referral delay.…”
Section: Intervention Typementioning
confidence: 99%